PENGETAHUAN DAN SIKAP TERHADAP GAYA HIDUP PADA PENDERITA DIABETES MELITUS DI PUSKESMAS GE’TENGAN - Lukas Siamben, Adolfina; Wijaya, Suharnita; Indrawati Ledianan Barung, Sri (NHM PRESS, 2024)
Increased sugar in the blood because it accumulates in the body due to disruption of hormones that function to lower sugar levels called diabetes mellitus. Knowledge about diabetes mellitus is very important. Perception or congnitiveness is the most important area for determining a person's behavior. Knowledge is essential to stimulate attitudes and stimuli towards action. The purpose of this study is to determine the relationship between knowledge and attitudes towards lifestyle in people with diabetes mellitus at Ge'tengan Tana Toraja Health Center. This type of research is quantitative research using a crossnsectional approach. With the technique of